1964
DOI: 10.1530/jrf.0.0080139
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Delayed Implantation in Rats by Means of an Intrauterine Foreign Body

Abstract: Summary. The presence of a foreign body in the uterine horn prevented implantation in rats when the process was delayed experimentally for 6 days. The contralateral horn, however, showed normal implantations. Colony-bred mature female rats weighing 120 to 130 g were used in this study. They were maintained under uniform laboratory conditions throughout the ex¬ perimental period. A surgical silk suture was inserted through the antimeso¬ metrial wall of the right uterine horn by an atraumatic needle under ether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1966
1966
1974
1974

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…This is in contrast with the finding of Doyle & Margolis (1963, 1965, Kar et al (1964) and Marston & Chang (1965), who found that the thread completely prevents implantation. Hence differences in methods must be considered.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with the finding of Doyle & Margolis (1963, 1965, Kar et al (1964) and Marston & Chang (1965), who found that the thread completely prevents implantation. Hence differences in methods must be considered.…”
Section: Discussioncontrasting
confidence: 99%
“…Greenwald used attached threads passing for 5 mm through the tissue of the horn. The length of the threads in our own experiments was 5 to 8 mm and thus differs only from those used by Kar et al (1964). Only threads passing through the lumen prevent implantation according to Greenwald. In our experiments it could be shown that even such threads do not always prevent implantation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Results from investigations in rabbits (Carleton & Phelps, 1933;Eckstein & Adams, 1964), rats (Doyle & Margolis, 1963;Kar, Kamboj & Datta, 1964;Chaudhury, 1964;, rumi¬ nants (Hawk, Conley, Brinsfield & Righter, 1964), and monkeys (Mastroianni & Hongsonand, 1964) have shown that although an iufb is effective in varying degrees in all these species, the time and mode of action differ. The animals studied thus far, however, also differ widely in one or more aspects of their reproductive anatomy and/or physiology.…”
Section: Introductionmentioning
confidence: 99%